The Gut Microbiota-Brain Axis: A New Frontier on Neuropsychiatric Disorders - Queiroz, Sarha A. L.; Ton, Alyne M. M.; Pereira, Thiago M. C.; Campagnaro, Bianca P.; Martinelli, Larissa; Picos, Aitor; Campos-Toimil, Manuel; Vasquez, Elisardo C. (Frontiers in Psychiatry, 2022)
Alzheimer’s disease (AD) is a progressive and incurable neurodegenerative disorder of integrative areas of the brain, characterized by cognitive decline and disability resulting in negative impacts on the family of the patients and the health care services worldwide. AD involves oxidative stress, neuroinflammation and accelerated apoptosis, accompanied by deposition of amyloid-β peptide plaques and tau protein-based neurofibrillary tangles in the central nervous system. Among the multiple factors that contribute to the onset and evolution of this disease, aging stands out. That is why the prevalence of this disease has increased due to the constant increase in life expectancy. In the hope of finding new, more effective methods to slow the progression of this disease, over the last two decades, researchers have promoted "omics"-based approaches that include the gut microbiota and their reciprocal interactions with different targets in the body. This scientific advance has also led to a better understanding of brain compartments and the mechanisms that affect the integrity of the blood-brain barrier. This review aims to discuss recent advances related to the gut-brain-microbiota axis in AD. Furthermore, considering that AD involves psychiatric symptoms, this review also focuses on the psychiatric factors that interact with this axis (an issue that has not yet been sufficiently addressed in the literature.